Impact of the Lockdown Due to the COVID-19 Pandemic on Patients With Inflammatory Bowel Disease - Nishida, Yu; Hosomi, Shuhei; Fujimoto, Koji; Nakata, Rieko; Sugita, Naoko; Itani, Shigehiro; Nadatani, Yuji; Fukunaga, Shusei; Otani, Koji; Tanaka, Fumio; Nagami, Yasuaki; Taira, Koichi; et al. (Frontiers in Medicine, 2021)
Background: The government of Japan declared a state of emergency on April 16, 2020, owing to the coronavirus disease 2019 (COVID-19) pandemic. The subsequent lockdown altered lifestyles and worsened mental illnesses. Inflammatory bowel disease (IBD) is an intestinal disorder that is affected by environmental factors. Therefore, we aimed to assess the effects of COVID-19 and the state of emergency on the lifestyle and disease activity of patients with IBD. Methods: We conducted a questionnaire survey on patients with IBD from June 16 to August 21, 2020 during their regular follow-up at our hospital, 2 months after the state of emergency was declared. Results: Overall, 241 patients with ulcerative colitis (UC) and 210 with Crohn’s disease (CD) completed the survey, of which 82 (34%) and 97 (46%) patients, respectively, reported disease exacerbation within 2 months after the lockdown. Multivariate logistic regression analysis identified age at enrollment (odds ratio, OR 0.98, 95% CI 0.96–0.99; P < 0.05), sleep hours (OR, 0.74; 95% CI, 0.57–0.97; P < 0.05), and increased stress due to the COVID-19 pandemic (OR, 6.06; 95% CI, 1.79–20.50; P < 0.01) as independent factors associated with UC exacerbation. Patients with exacerbated CD were younger at CD onset and had higher patient-reported outcome 2 scores before the state of emergency than patients with non-exacerbated CD. On multivariate analysis, age (OR, 0.97; 95% CI, 0.95–0.99; P < 0.01) and active disease before the state of emergency (OR, 2.20; 95% CI, 1.23–3.95; P < 0.01) were independently associated with CD exacerbation. Conclusions: Improving sleep quality and preventing psychological stress may be crucial in IBD management during a pandemic, especially in young patients.